Characteristic Processes in Close Peer Friendships of Preterm Infants at Age 12. (2nd September 2012) - Sullivan, Mary C.; Barcelos Winchester, Suzy; Parker, Jeffrey G.; Marks, Amy K.
Abstract : Close friendships become important at middle-school age and are unexplored in adolescents born prematurely. The study aimed to characterize friendship behaviors of formerly preterm infants at age 12 and explore similarities and differences between preterm and full-term peers on dyadic friendship types. From the full sample ofN = 186, one hundred sixty-six 12-year-old adolescents (40 born full term, 126 born preterm) invited a close friend to a 1.5 hour videotaped laboratory play session. Twenty adolescents were unable to participate due to scheduling conflicts or developmental disability. Characteristic friendship behaviors were identified by Q-sort followed by Q-factoring analysis. Friendship duration, age, and contact differed between the full-term and preterm groups but friendship activities, behaviors, and quality were similar despite school service use. Three Q-factors, leadership, distancing, and mutual playfulness, were most characteristic of all dyads, regardless of prematurity. These prospective, longitudinal findings demonstrate diminished prematurity effects at adolescence in peer friendship behavior and reveal interpersonal dyadic processes that are important to peer group affiliation and other areas of competence.